2007
DOI: 10.1080/09548980701671094
|View full text |Cite
|
Sign up to set email alerts
|

Human eye-head co-ordination in natural exploration

Abstract: During natural behavior humans continuously adjust their gaze by moving head and eyes, yielding rich dynamics of the retinal input. Sensory coding models, however, typically assume visual input as smooth or a sequence of static images interleaved by volitional gaze shifts. Are these assumptions valid during free exploration behavior in natural environments? We used an innovative technique to simultaneously record gaze and head movements in humans, who freely explored various environments (forest, train station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 64 publications
5
79
1
Order By: Relevance
“…Although we did not measure eye position in our study, it has been shown that changes in gaze direction are generally implemented by a combination of eye and head movements in the same direction (Barnes 1979;Guitton and Volle 1987). This is especially true for large gaze shifts (Einhäuser et al 2007). For example, during a simple walking task consisting of a 90° turn it has been found that the eyes smoothly lead the head by looking further into the direction of turning (Imai et al 2001).…”
Section: Relative Head Yaw During Turnsmentioning
confidence: 88%
“…Although we did not measure eye position in our study, it has been shown that changes in gaze direction are generally implemented by a combination of eye and head movements in the same direction (Barnes 1979;Guitton and Volle 1987). This is especially true for large gaze shifts (Einhäuser et al 2007). For example, during a simple walking task consisting of a 90° turn it has been found that the eyes smoothly lead the head by looking further into the direction of turning (Imai et al 2001).…”
Section: Relative Head Yaw During Turnsmentioning
confidence: 88%
“…In those studies, the image was presented statically, but in our present study, it was used as the source for a one-dimensional movie by iterating row-wise through the source image: Each row was stretched vertically in space and presented as a frame ( Figure 2); the movie thus appeared as a flickering bar code. The choice of spatial one-dimensionality was done for technical simplicity, but is justifiable by the fact that a large number of saccades are made along the cardinal axes (Einhäuser et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that during the human walk the head moves in a horizontal plane from side to side [7,13]. Head motion is observed not only in humans, but also for animals.…”
Section: Introductionmentioning
confidence: 99%